The transient effect of dexamethasone on foetal cardiotocography in antenatal period - Kandoria, Meenakshi; Agnihotri, Sarita; Thakur, Kajal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preterm birth is a major contributor to neonatal morbidity and mortality worldwide. This study aimed to evaluate the impact of antenatal dexamethasone on CTG patterns, specifically FHR variability, accelerations, and foetal movements, in women at high risk of preterm labour. Methods: A cross-sectional, comparative observational study was conducted in a Kamla Nehru hospital Shimla from June 23 to June 24. The study included 102 women aged 18-35 years, with a gestational age of 28-34 weeks, at risk for preterm delivery. Participants received a full course of dexamethasone (24 mg in divided doses 12 hours apart). CTG was recorded before administration and at 48- and 96-hours post-dexamethasone. Statistical analysis was performed using Chi-square tests with significance set at p<0.05. Results: Before dexamethasone administration, all participants reported normal foetal movement, but 48 hours later, 53.9% reported decreased foetal movement (p<0.001). By 96 hours, the perception of foetal movement returned to normal in 98% of participants (p=0.498). FHR variability significantly decreased with moderate variability observed in 74.5% of cases at 48 hours (p<0.001). FHR accelerations decreased significantly from 94.1% before administration to 79.4% at 48 hours (p=0.002), but returned to baseline by 96 hours (p=0.774). Conclusions: Dexamethasone administration resulted in transient changes in FHR patterns, including decreased accelerations, decreased moderate variability, and reduced foetal movement within the first 48 hours. However, these effects were short-lived, with normalization occurring by 96 hours.